The Effects of Circadian Rhythm on Lead-Induced Toxicity in the DBC1.2 Olfactory Dark Basal Cell Line - Teru Kamogashira; Shu Kikuta; Tatsuya Yamasoba (Cells)
Background/Objectives: This study evaluated changes in circadian clock genes and mitochondrial function in a lead (Pb)-induced toxicity model of an olfactory epithelial cell line. Methods: The DBC1.2 olfactory dark basal cell line was used. Dexamethasone shock was used to reset the circadian clock 24 h (Group 1) and 36 h (Group 2) after seeding. Then, 60 h after seeding, the cells were treated with or without Pb (II) nitrate in HEPES buffer for 1 h. Mitochondrial function and cell viability were evaluated 84 h after seeding. Results: Mitochondrial function under Pb exposure was significantly impaired in Group 1 compared with Group 2. Cell numbers and viability did not significantly differ between groups. The mitochondrial membrane potential was significantly higher in Group 1 than Group 2, both without and with Pb exposure. Conclusions: The circadian rhythm can alter the sensitivity to Pb-induced toxicity and mitochondrial damage in olfactory cells.